2021
DOI: 10.3341/jkos.2021.62.7.881
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Endonasal Dacryocystorhinostomy with Nasal and Lacrimal Sac Mucosal Flaps

Abstract: Purpose: In patients with nasolacrimal duct obstruction, the outcomes of surgery were evaluated according to the type or presence of flaps. Methods: In total, 509 eyes were compared retrospectively: 178 eyes in patients treated without flaps, 126 eyes in patients treated using nasal mucosa flaps, and 205 eyes in the patient group using nasal and lacrimal sac mucosal flap were compared retrospectively. We analyzed the factors of success according to the surgical method by comparing granulation and bony ostium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In such cases, we recommend incision and enlargement of the anterior part of the sinus before conducting either partial or the entire surgical intervention within the ethmoid sinus. Conventionally, it was essential to form a single nasal sac flap and a single lacrimal sac flap and oppose them during En-DCR [2,[11][12]15,23] . In this study, however, we generated a large C-shaped lacrimal sac flap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases, we recommend incision and enlargement of the anterior part of the sinus before conducting either partial or the entire surgical intervention within the ethmoid sinus. Conventionally, it was essential to form a single nasal sac flap and a single lacrimal sac flap and oppose them during En-DCR [2,[11][12]15,23] . In this study, however, we generated a large C-shaped lacrimal sac flap.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in earlier studies, we demonstrated that supplementary use of Merogel enhances the success of En-DCR surgery for primary chronic dacryocystitis via promotion of early osteium reepithelialization, suppression of fibrotic tissue development at the ostium, and prevention of the lacrimal sac apposition to the nasal mucosa flaps [15,[29][30] . Based on literature, En-DCR has a success rate of 82.2%-95.6% [4,[10][11][12][13][24][25][26] . In this study, En-DCR was performed with a success rate of 93.0%, with complete attenuation of clinical symptoms post-surgery, and with an unobstructed lacrimal system, as evidenced by free-flowing irrigation of the system and nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation